2011
DOI: 10.1900/rds.2011.8.17
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas Transplantation: Lessons Learned From a Decade of Experience at Wake Forest Baptist Medical Center

Abstract: ■ AbstractThis article reviews the outcome of pancreas transplantations in diabetic recipients according to risk factors, surgical techniques, and immunosuppression management that evolved over the course of a decade at Wake Forest Baptist Medical Center. A randomized trial of alemtuzumab versus rabbit anti-thymocyte globulin (rATG) induction in simultaneous kidney-pancreas transplantation (SKPT) at our institution demonstrated lower rates of acute rejection and infection in the alemtuzumab group. Consequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 27 publications
0
47
0
Order By: Relevance
“…These islets have already shown longevity potential in humans. Human pancreas [13] and islet transplantations [14] result in varying degrees of insulin independence, with 5-yr independence rates >50% [15,16]. Nevertheless, the application of human tissue transplantation approaches to a large majority of T1D patients is hampered by the limiting supply of donor tissue [17].…”
Section: Introductionmentioning
confidence: 99%
“…These islets have already shown longevity potential in humans. Human pancreas [13] and islet transplantations [14] result in varying degrees of insulin independence, with 5-yr independence rates >50% [15,16]. Nevertheless, the application of human tissue transplantation approaches to a large majority of T1D patients is hampered by the limiting supply of donor tissue [17].…”
Section: Introductionmentioning
confidence: 99%
“…Indications for PT were insulin-requiring diabetes with complications and the predicted ability to tolerate the operative procedure and manage the requisite immunosuppression and close follow-up irrespective of C-peptide production [9,10]. Selection criteria for SKPT in "type 2" diabetes included patients <55 years of age with a body mass index (BMI) <30 kg/m2, insulin-requiring for a minimum of 3 years with a total daily insulin requirement <1 u/kg/ day, a fasting C-peptide level <10 ng/ml, absence of severe vascular disease or tobacco abuse, adequate cardiac function, and presence of "complicated" or hyperlabile diabetes [9,10].…”
Section: Recipient Selectionmentioning
confidence: 99%
“…Selection criteria for SKPT in "type 2" diabetes included patients <55 years of age with a body mass index (BMI) <30 kg/m2, insulin-requiring for a minimum of 3 years with a total daily insulin requirement <1 u/kg/ day, a fasting C-peptide level <10 ng/ml, absence of severe vascular disease or tobacco abuse, adequate cardiac function, and presence of "complicated" or hyperlabile diabetes [9,10]. Selection criteria for solitary PT were similar to SKPT except for renal function, in which the calculatedglomerular filtration rate was >70 ml/min/1.73m2 in PTA (native renal function) and >40 ml/min/1.73m2in PAK (renal allograft function) recipients who were already receiving a calcineurin inhibitor.…”
Section: Recipient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical settings, extracorporeal elimination is employed for the management of autoimmune diseases (removal of autoantibodies and immune complexes), cases of poisoning, sepsis, and organ transplantation. [76][77][78][79][80][81] In a series of studies, Tennvall et al have demonstrated the utility of extracorporeal affinity adsorption using avidin columns to deplete biotinylated radiolabeled antibodies from circulation. [82][83][84][85][86][87][88][89][90][91][92] In one of the earliest demonstrations of the approach using athymic rats bearing human melanoma and lung cancer xenografts, removal of biotinylated 125 I-labeled antimelanoma (MAb 96.5) and anticarcinoma (MAb L6) antibodies improved the tumor to normal tissue ratios by a factor of four or five.…”
mentioning
confidence: 99%